Periodic Collapsed Solid-Core PCF Based Modal Interferometer for Chemical Sensing - Dash, Jitendra Narayan; Jha, Rajan (Frontiers in Sensors, 2022)
We experimentally demonstrated a periodically collapsed solid core photonic crystal fiber (SCPCF) based modal interferometer for sensing refractive index (R.I) of chemicals. A given piece of SCPCF is periodically collapsed using an easily and widely available commercial splicer machine and a micro positioner. The distance between collapsed and number of collapsed regions can be controlled precisely by the inexpensive micro positioner. The effect of number of periods on the RI sensitivity has been studied. Our experimental results show that this simple and easily fabricated interferometer has RI sensitivity of 230 nm/RIU with negligible cross temperature error.